Hubungan Pengetahuan tentang Makanan Sehat dan Kebiasaan Konsumsi Jajanan dengan Kejadian Diare pada Siswa SDN 81 Manado - Bahagia Djarangkala; Kritine Dareda; Sri Wahyuni (CV. ALIM'SPUBLISHING, 2026)
Diarrhea is a common health problem among school-aged children. Factors influencing its occurrence include knowledge of healthy food and the habit of consuming snacks within the school environment. The objective of this research was to examine the relationship between knowledge of healthy food and snack consumption habits with diarrhea cases at SDN 81 Manado. This research employed a descriptive-analytic design with a cross-sectional approach. A total of 50 respondents were selected based on inclusion and exclusion criteria. Data collection was conducted using questionnaires addressing both variables. Statistical analysis was performed using the Chi-Square test with a significance level of ρ ≤ 0.05. The findings revealed that 35 respondents (75.0%) had poor knowledge of healthy food, and 32 respondents (64.0%) experienced diarrhea. Additionally, 42 respondents (84.0%) reported poor snack consumption habits, with 37 respondents (74.0%) experiencing diarrhea (29 males and 21 females). Chi-Square analysis produced a ρ-value of 0.001, which is lower than the alpha level (α = 0.05), indicating a significant relationship between knowledge of healthy food, snack consumption habits, and diarrhea cases. The study concludes that both knowledge of healthy food and snack consumption habits are significantly associated with diarrhea among school-aged children. Parental involvement is essential in educating children about healthy food choices as a preventive measure against diarrhea.